Using Mind Maps as a Teaching and Learning Tool to Promote Student Engagement - As'ari As'ari (English Education Department, 2017)
Creating an environment that engages students in the learning journey is not always easy. Sometimes as faculty members we ask ourselves, “Are we taking this learning journey by ourselves?” Several years ago as I began my scholarly exploration of the utility of mind mapping as a teaching and learning tool to foster critical thinking, my colleague and I instituted a mind mapping learning activity which has helped to promote student engagement in the classroom. So what is mind mapping? Mind mapping is a learning technique which uses a non-linear approach to learning that forces the learner to think and explore concepts using visual partial relationships flowing from a central theme to peripheral branches which can be inter- related. According to Buzan and Buzan, a mind map should be drawn on blank paper that is larger than standard 8 ½ by 11 inch paper. The rationale behind using a large sheet of paper is that it allows the student the opportunity to break away from the boundaries established by standard sized paper. The medium for drawing the mind map is usually colored pens or pencils. Students begin by drawing an image in the center of the paper that reflects the central theme, or topic, of the mind map which is to be created. By placing this central image in the center of the paper it allows the student 360 degrees of freedom to develop their mind map. Next, the student draws main branches with key words extending from this central image. The branches represent different categories which the student perceives as being relevant to the content of the key concept of the mind map. From these main branches, sub-branches are created.